Systematic reviews of health effects of social interventions: 1. Finding the evidence: how far should you go?. Issue 9 (12th August 2005) - Ogilvie, David; Hamilton, Val; Egan, Matt; Petticrew, Mark
Abstract : Study objective: There is little guidance on how to identify useful evidence about the health effects of social interventions. The aim of this study was to assess the value of different ways of finding this type of information. Design: Retrospective analysis of the sources of studies for one systematic review. Setting: Case study of a systematic review of the effectiveness of interventions in promoting a population shift from using cars towards walking and cycling. Main results: Only four of the 69 relevant studies were found in a "first-line" health database such as Medline. About half of all relevant studies were found through the specialist Transport database. Nine relevant studies were found through purposive internet searches and seven relevant studies were found by chance. The unique contribution of experts was not to identify additional studies, but to provide more information about those already found in the literature. Conclusions: Most of the evidence needed for this review was not found in studies indexed in familiar literature databases. Applying a sensitive search strategy across multiple databases and interfaces is very labour intensive. Retrospective analysis suggests that a more efficient method might have been to search a few key resources, then to ask authors and experts directly for the most robust reports of studies identified. However, internet publications and serendipitous discoveries did make a significant contribution to the total set of relevant evidence. Undertaking a comprehensive search may provide unique evidence and insights that would not be obtained using a more focused search.